Pendampingan Terapi Kelompok untuk Menurunkan Kecenderungan Perilaku Bullying pada Siswa SDN 1 Ketindan Kec. Lawang - Chantika Mahadini; Mayang Wulandari (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background : Bullying behavior is a crime committed by children, so this behavior is considered abnormal, because it will have a negative impact on the victim. Purpose : Community service activities in the form of group assistance aimed at reducing bullying behavior in students of SDN 1 Ketindan Lawang. Methods : The method offered for partner problems is activities in the form of counseling about bullying and group assistance to students who have a tendency to bullying behavior. The method of implementing community service is in the form of counseling and group mentoring methods consisting of 4 sessions. Result : The result of this community service activity is that partner groups can understand and identify bullying and partner groups can reduce bullying tendencies. Conclusion :Bullying tendencies can be prevented by providing an understanding and educational approach in the form of conditioning good behavior as early as possible for students.